Effect of Ramadan fasting on platelet aggregation in healthy male subjects - Aybak, M; Turkoglu, A; Sermet, A; Denli, O (Springer, 1996)
The purpose of this study was to examine platelet aggregation during Ramadan fasting. A group of 20 healthy non-smoking male volunteers were studied, whose mean age was [21 (SD 2.4) years range 19-24]. The average fast was about 15 h. Venous blood samples were taken on 4 different days; 1 day before Ramadan (day 0), then on the 1st, 14th and 28th day of Ramadan, On each of these 4 days, blood samples were taken at 4 p.m. (1 h before the evening meal). Body mass index and platelet count did nor change during fasting. Bleeding and coagulation time had increased significantly by the end of Ramadan fasting (P < 0.05, P < 0.005 respectively), but these changes remained within physiological Limits. Ramadan fasting induced a reduction in platelet sensitivity to adenosine 5'-diphosphate (ADP) and collagen on days 14 (P < 0.05) and 28 (P < 0.05, P < 0.005 respectively). However, adrenaline-induced. platelet aggregation decreased only on day 25 (P < 0.05). This study indicated that Ramadan fasting led to a decrease in the platelet responses of different aggregating agents (ADP, adrenaline and collagen) in vitro. It also led to an increase in bleeding and coagulation time.
Keywords: Ramadan fasting; platelet aggregation; blood lipids; glucose